Answer:
c. (3, 2)
Step-by-step explanation:
Equating the values of y :
- -x + 5 = x - 1
- x + x = 5 + 1
- 2x = 6
- <u>x = 3</u> [x-coordinate of the solution]
Finding y by substituting x in one of the equations :
- y = x - 1
- y = 3 - 1
- <u>y = 2</u> [y-coordinate of the solution]
Solving :
- Solution = (x, y)
- Solution = (3, 2)
Answer:
p=25
Step-by-step explanation:
-5[-9=-
-4] Get rid of the fraction by multiplying the whole equation by -5.
45=p+20 Then, subtract 20 from both sides.
25=p
The trick here is to notice that all 3 terms can be div. by 2:
2(x^2 + x - 12)
Note that -12 factors into -3 * 4 or -4 * 3. Thus,
x^2 + x - 12 = (x-4)(x+3), and so <span>2x2 + 2x − 24 = 2(x-4)(x+3).</span>
Answer:
Step-by-step explanation:
-2.8f + 0.7f - 14 - 4
- 2.1f - 18
Since it is a square that means each side is equal.
The perimeter is 24, and since there is four sides we would divide it by four to find the length of each side.
24/4 = 6
Each side is 6.
By looking at the picture, one side of the square, is the length of the radius.
The radius of the square is 6.
The only thing left to do is to find the circumference.
The circumference formulas are:
C =

d
C = 2

r
We can use the first one Diameter x pi (3.14)
To find the diameter we would just multiply the radius by two.
6 x 2 = 12
Diameter = 12
So multiply it by pi
12 x 3.14 = 37.68
or D 12